"The More You Know": Critical Historical Knowledge About Indian Residential Schools Increases Non‐Indigenous Canadians' Empathy for Indigenous Peoples. Issue 4 (25th September 2021) - Neufeld, Katelin H. S.; Starzyk, Katherine B.; Boese, Gregory D.; Efimoff, Iloradanon H.; Wright, Stephen
Abstract : The pursuit of intergroup reconciliation often includes efforts to educate with the goal of fostering empathy. Yet little empirical evidence demonstrates whether and why greater knowledge might increase empathy. In this research, we investigated whether more critical historical knowledge about a harmed outgroup increases empathy for them, and we explored whether perceptions of privity, the extent to which a past harm continues to cause suffering today, account for this relationship. We tested these hypotheses in the context of non‐Indigenous Canadians' knowledge of Indian Residential Schools and attitudes about Indigenous Peoples across eight laboratory studies with 1242 non‐Indigenous undergraduate students at two Canadian universities. In two studies, participants completed a multiple‐choice measure of knowledge. In the remaining studies, we experimentally varied knowledge through brief educational interventions. All studies included measures of empathy, and five studies included measures of privity. Internal meta‐analyses indicated that participants with higher levels of critical historical knowledge felt more empathy for the outgroup because they could better see how past intergroup harms continue to cause suffering today. We discuss implications for social and political psychological theory and designing education for reconciliation interventions in Canada and elsewhere.